2006
DOI: 10.1143/jpsj.75.074707
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and a Mott Transition in a Hubbard Model on an Anisotropic Triangular Lattice

Abstract: A half-filled-band Hubbard model on an anisotropic triangular lattice (t in two bond directions and t ′ in the other) is studied using an optimization variational Monte Carlo method, to consider a Mott transition and superconductivity arising in κ-(BEDT-TTF)2X. Adopting wave functions with doublon-holon binding factors, we reveal that a first-order Mott (conductorto-nonmagnetic insulator) transition takes place at U = Uc, approximately of the bandwidth, for a wide t ′ /t range. This transition is not directly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 63 publications
(17 reference statements)
8
114
1
Order By: Relevance
“…It is well known that the perfect nesting of the square lattice means that is insulating for arbitrarily small U/t. For t = t, it is found, numerically, that the Mott transition occurs at around U/t = 10-15, depending on the method used [3,[15][16][17][18][19][20][21]79]. The metal-insulator transition line in Fig.…”
Section: Comparison With Organicsmentioning
confidence: 95%
See 1 more Smart Citation
“…It is well known that the perfect nesting of the square lattice means that is insulating for arbitrarily small U/t. For t = t, it is found, numerically, that the Mott transition occurs at around U/t = 10-15, depending on the method used [3,[15][16][17][18][19][20][21]79]. The metal-insulator transition line in Fig.…”
Section: Comparison With Organicsmentioning
confidence: 95%
“…This model contains three parameters: U the effective on-site Coulomb repulsion, t the nearest-neighbor hopping integral, and t the next-nearest-neighbor hopping integral along one diagonal only. The Hubbard model on the anisotropic triangular lattice has been studied via a number of approaches [15][16][17][18][19][20][21]. Some methods have suggested that a spin liquid is realized in the insulating phase.…”
Section: Introductionmentioning
confidence: 99%
“…E is symmetric with respect to t ′ /t = 0 owing to the electron-hole symmetry. 35 Similarly to the case on the frustrated square lattice, E(FS) and E(d−SC) (if the band renormalization is considered 115,116 ) are constant. For the ground state, we find from Fig.…”
Section: Anisotropic Triangular Latticementioning
confidence: 98%
“…What is interesting though is that the proposed scenario can give a unified approach to SC in all organic CTS, irrespective of whether the insulating state proximate to SC is AFM 102 , CO 67,103 or VBS 82 . Recall that within existing mean field theories the AFM-to-SC transition is driven by spin fluctuations [13][14][15][16][17][18][19][20][21][22][23] , while the CO-to-SC transition is driven by charge fluctuations 65 . Even if we ignore that recent precise numerical calculations [25][26][27] have demonstrated the absence of SC within the proposed spin-fluctuation models in this context (thereby raising doubts also about mean-field theory of charge-fluctuation mediated superconductivity), different mechanisms of SC for structurally related materials with identical or nearidentical molecular components appear to be unrealistic.…”
Section: Consequence Of Stronger Frustration-paired Electron Liquid Amentioning
confidence: 99%
“…An extension of the RVB theory of dopant-induced SC in ρ = 1 is the proposal that frustration-induced SC occurs in the anisotropic triangular lattice within the simple Hubbard model even for ρ exactly 1, where a narrow superconducting phase is straddled on both sides by broader PM and AFM insulator phases [13][14][15][16][17][18][19][20][21][22][23] . It has been claimed that this transition explains the SC in the CTS [13][14][15][16][17][18][19][20][21][22][23][24] . Recent numerical work by us and others, however, have determined that SC is absent within the ρ = 1 triangular lattice Hubbard model [25][26][27] and the earlier results are artifacts of mean-field approximations.…”
mentioning
confidence: 99%